Immunoelectron microscopic identification and localization of Streptococcus sanguis with peroxidase-labeled antibody: localization of surface antigens in pure cultures. - Lai, C H (1975)
An indirect method of localizing antigens with horseradish peroxidase-labeled antibody was used to identify and localize surface antigens of Streptococcus sanguis at the ultrastructural level. An electron dense layer surrounding the cell wall could be distinguished without any additional electron microscope staining. This labeled layer represents an immune complex consisting of bacterial surface antigens, specific rabbit antisera, and peroxidase-labeled goat anti-rabbit globulins. Although with undiluted antisera slight cross-reactions occurred with S. salivarius and S. miteor (mitis), these could be readily distinguished from the more intense homologous reaction by their patchiness and the difference in distribution of the label. These cross-reactions were eliminated by appropriate dilutions of the antiserum. No cross-reactions occurred with S. mutans, S. faecalis, Actinomyces species, or Bacterionema, microorganisms wents indicated that horseradish peroxidase can become non-specifically adsorbed to the membrane of certain bacterial cells. Appropriate controls must, therefore, be included for localization of membrane associated antigens with horseradish peroxidase.